2023
DOI: 10.1108/ijoem-12-2021-1878
|View full text |Cite
|
Sign up to set email alerts
|

Foreign direct investment by multinational corporations in emerging economies: a comprehensive bibliometric analysis

Abstract: PurposeThis study introduces a comprehensive bibliometric analysis of the foreign direct investment (FDI) literature by multinational corporations (MNCs) focusing on emerging economies to identify the most influential authors, journals and articles in FDI research and reveals the fields' conceptual and intellectual structures. The purpose of this paper is to address these issues.Design/methodology/approachThe study analyzed 533 articles published between 1974 and 2020 in 226 academic journals indexed in the We… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(1 citation statement)
references
References 108 publications
0
1
0
Order By: Relevance
“…This has shaped the foreign investment policies of most low-income countries, which are designed to attract foreign firms such as TNCs (Pandya, 2016). According to Nazzal et al (2023), TNCs contribute to the host country's economic development by improving standards of living through direct employment of local people, bringing in foreign currency and advanced technology, as well as increasing the host country's revenues and hence gross domestic product. Scholars have reported that low-income countries benefit more from foreign investments (Coetzee et al, 2016;Xiao & Tian, 2023).…”
Section: Introductionmentioning
confidence: 99%
“…This has shaped the foreign investment policies of most low-income countries, which are designed to attract foreign firms such as TNCs (Pandya, 2016). According to Nazzal et al (2023), TNCs contribute to the host country's economic development by improving standards of living through direct employment of local people, bringing in foreign currency and advanced technology, as well as increasing the host country's revenues and hence gross domestic product. Scholars have reported that low-income countries benefit more from foreign investments (Coetzee et al, 2016;Xiao & Tian, 2023).…”
Section: Introductionmentioning
confidence: 99%